Bisakah PNS Melayani Secara Efektif Selama COVID-19? Studi Kebijakan Work from Home Di Dinas Sosial Kabupaten Sleman: Can Civil Servants Serve Effectively During COVID-19? Study of Work from Home Policy in the Department of Social Service of Sleman Regency - Al Fauzi Rahmat (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2021)
The outbreak of Corona Virus Disease (Covid-19) cases in various countries, including Indonesia, resulted in the paralysis of most services, including in the government sectors. The enactment of Work from Home (WFH) policy for State Civil Servants (PNS) indicates the massive level of urgency for the spread of this deadly virus, leading to the Social Distance policy being also applied in the government environment. This article aims to examine civil servants' work effectiveness in implementing WFH during Covid-19 pandemic in Sleman Regency, with a case study at the Department of Social Service. This research uses an exploratory case study approach, emphasizing the exploration of a phenomenon such as WFH policy. Furthermore, semi-structured interviews and literature reviews were used to obtain reliable data analysis. The findings of this study show that the adaptation of civil servants in the Sleman Social Service to the WFH policy is seen as complex in several divisions, because they are not accustomed to working in a home environment where teleconference facilities may be urgently required and the dependence on communication and coordination between employees is crucial. Another issue is that in the Department of Social Service there are no sanctions for civil servants who do not work under the guidance of WFH policy. In addition, knowledge and skills needed to operate and administer online services are still limited, affecting civil servants' ability in delivering a community’s public service needs. Hence, the implementation of WFH policy may not be effective in all types of public operations.